How did Japan catch-up with the West? Some implications or recent revisions to Japan’s historical growth record - Broadberry, S; Fukao, K; Settsu, T (University of Oxford, 2025)
This paper uses recently revised data on Japanese GDP to analyse the process by which Japan caught-up with the West. The new historical national accounts suggest that Japan was more than one-third richer in 1874 than suggested by Maddison, and that the Meiji period growth built on earlier development. We show that (1) despite trend GDP per capita growth during the Tokugawa shogunate, the catching-up process only started after 1890 with respect to Britain, and after World War 1 with respect to the United States and many European nations (2) although catching up was driven by the dynamic productivity performance of Japanese manufacturing, Japanese success in exporting manufactured goods was just as much driven by limiting the growth of real wages (3) despite claims that Japan was following a distinctive Asian path of labour intensive industrialisation, capital played an important role in the catching-up process.